Evolutionary algorithms and fuzzy sets for discovering temporal rules - Matthews, Stephen G.; Gongora, Mario A.; Hopgood, Adrian A. (Zielona Góra: Uniwersytet Zielonogórski)
A novel method is presented for mining fuzzy association rules that have a temporal pattern. Our proposed method contributes towards discovering temporal patterns that could otherwise be lost from defining the membership functions before the mining process. The novelty of this research lies in exploring the composition of fuzzy and temporal association rules, and using a multi-objective evolutionary algorithm combined with iterative rule learning to mine many rules.
Keywords: fuzzy association rules; temporal association rules; multi-objective evolutionary algorithm